Marketing, Business Processes, and Shareholder Value: An Organizationally Embedded View of Marketing Activities and the Discipline of Marketing - SRIVASTAVA, Rajendra Kumar (Institutional Knowledge at Singapore Management University, 1999)
The authors develop a framework for understanding the integration of marketing with business processes and shareholder value. The framework redefines marketing phenomena as embedded in three core business processes that generate value for customers-product development management, supply chain management, and customer relationship management-which in turn creates shareholder value. Such a conceptualization of marketing has the potential to introduce dramatic shifts in the scope, content, and influence of marketing in the organization. The authors highlight the implications of an organizationally embedded view of marketing for the future of marketing theory and practice.